Novos enquadramentos culturais na relação estado e mercado entre 2003 e 2012: um estudo de caso dos arcabouços culturais, normativos e financeiros das PPP Belo Monte e Jirau no PAC - Silva, Márcio Rogério (Universidade Federal de São Carlos, 2013)
The research aims to present the new cultural framework in relationship of state and market of leaders in governments understood groups between 2003 and 2012, where this framework is understood as moral content in the background of monetary policy, limitations imposed by the current financial and cultural search for legitimacy of the multiple interests of civil society through convergence of elites based Grun (2005) and stretching circuit legitimation. Another important point of the study is to point the government as an articulator of public and private interests with considerable control via economic capital. With support of economic sociology and finance, based on the definitions of Svedberg (2009), first analyzes is the economic phenomena, which are presented as the government exerts control in the institutions that define the Public-Private Partnership (PPP) in the Accelerated Growth Plan (PAC) , with emphasis on hydroelectric plants analyzed (Belo Monte and Jirau) by through their financial institutions and companies. The government makes use of monetary policy, with tax cuts and financing via Treasury, to finance productive capital and infrastructure in the PAC, with relevant shareholdings via Eletrobras and pension funds Petros, Previ and FUNCEF, indicating moral teachings in the use of money in terms of Neiburg (2010). Are analyzed economically conditioned phenomena. Based on Simmel (1998), the formation of economic life influences the psychic and cultural situation of a time and receives on the other hand the great currents of homogeneous historical life (Taylorism, finance and democratization process of the country), with values that spread through society. To understand the origins of the social justification of use of finance as a tool for social inclusion through the market, we found evidence discursive norms on capital and generation of employment and income, the federal government and specifically the institutions of the eletric sector, and in the consortia Northern Energy and Enersus. Finally it was shown how society influences economic phenomena, with considerations on the convergence of elites based Grun (2005) and stretching circuits legitimacy, and new strategies by the opponents of the current development policy, highlighting the PLATAFORMA BNDES.
Keywords: Sociologia econômica; Privatização; Política monetária; Parcerias público-privadas; Políticas públicas; Setor elétrico; Privatization; Public-private partnerships; Plan to accelerate growth; Electricity sector; ENGENHARIAS::ENGENHARIA DE PRODUCAO